Go With Your Gut: The Shaping of T-Cell Response by Gut Microbiota in Allergic Asthma - Di Gangi, Alessandro; Di Cicco, Maria Elisa; Comberiati, Pasquale; Peroni, Diego G. (Frontiers in Immunology, 2020)
Novel methods in immunological research and microbiome evaluation have dramatically changed several paradigms associated with the pathogenesis of allergic asthma (AAS). Ovalbumin and house dust mite-induced AAS in germ-free or specific pathogen-free mice are the two leading experimental platforms that significantly contribute to elucidate the relationship between AAS and gut microbiota. Beyond the exacerbation of T helper (Th) 2 responses, a complex network of immunological interaction driven by gut microbiota could modulate the final effector phase. Regulatory T cells are abundant in gastrointestinal mucosa and have been shown to be pivotal in AAS. The gut microbiota could also influence the activity of other T cell subsets such as Th9, Th17, and populations of effector/memory T lymphocytes. Furthermore, gut microbiota metabolites drive the hematopoietic pattern of dendritic cells and ameliorates lung Th2 immunity in AAS models. The administration of probiotics has shown conflicting results in AAS, and limited evidence is available on the immunological pathways beyond their activity. Moreover, the impact of early-life gut dysbiosis on AAS is well-known both experimentally and clinically, but discrepancies are observed between preclinical and clinical settings. Herein, our aim is to elucidate the most relevant preclinical and clinical scenarios to enlighten the potential role of the gut microbiota in modulating T lymphocytes activity in AAS.